Examining the Effect of Adverbs and Onomatopoeia on Physical Movement - Irie, Keisuke; Zhao, Shuo; Okamoto, Kazuhiro; Liang, Nan (Frontiers in Psychology, 2021)
Introduction: The effect of promoting a physical reaction by the described action is called the action-sentence compatibility effect (ACE). It has been verified that physical motion changes depending on the time phase and grammatical expression. However, it is unclear how adverbs and onomatopoeia change motion simulations and subsequent movements. Method: The subjects were 35 healthy adults (11 females; mean age 21.3). We prepared 20 sentences each, expressing actions related to hands and feet. These were converted into 80 sentences (stimulus set A), with the words “Slow” or “Quick” added to the words related to the speed of movement, and 80 sentences (stimulus set B) with the words “Fast” and onomatopoeia “Satto” added. Additionally, 20 unnatural sentences were prepared for each stimulus set as pseudo sentences. Choice reaction time was adopted; subjects pressed the button with their right hand only when the presented text was correctly understood (Go no-go task). The reaction time (RTs) and the number of errors (NoE) were recorded and compared. Results: As a result of a two-way repeated ANOVA, an interaction effect (body parts × words) was observed in RTs and NoE in set A. “Hand and Fast” had significantly faster RTs than “Hand and Slow” and “Foot and Fast.” Furthermore, “Hand and Fast” had a significantly higher NoE than others. In set B, the main effects were observed in both RTs and NoE. “Hand” and “Satto” had significantly faster RTs than “Foot” and “Quick,” respectively. Additionally, an interaction effect was observed in NoE, wherein “Foot and Satto” was significantly higher than “Hand and Satto” and “Foot and Quick.” Conclusion: In this study, the word “Fast” promoted hand response, reaffirming ACE. The onomatopoeia “Satto” was a word that conveys the speed of movement, but it was suggested that the degree of understanding may be influenced by the body part and the attributes of the subject.